Safety of integrated preventive chemotherapy for neglected tropical diseases. - Allan M Ciciriello; Jessica K Fairley; Emma Cooke; Paul M Emerson; Pamela J Hooper; Birgit Bolton; Genevieve LaCon; David G Addiss (PLoS Neglected Tropical Diseases, 2022)
Background Preventive chemotherapy (PC) is a central strategy for control and elimination of neglected tropical diseases (NTDs). Increased emphasis has been given to "integration" of NTD programs within health systems and coadministration of NTD drugs offers significant programmatic benefits. Guidance from the World Health Organization (WHO) reflects current evidence for safe drug coadministration and highlights measures to prevent choking of young children during PC. Methodology To understand how coadministration of NTD drugs might affect PC safety, we reviewed literature on choking risk in young children and safety of coadministered NTD drugs. To understand current practices of drug coadministration, we surveyed 15 NTD program managers and implementing partners. Principal findings In high-income countries, choking on medication is an infrequent cause of death in young children. In low-resource settings, data are limited, but age-appropriate drug formulations are less available. During PC, fatal choking, although infrequent, occurs primarily in young children; forcing them to swallow tablets appears to be the major risk factor. The WHO currently recommends 6 drugs and 5 possible drug combinations for use in PC. Of 105 nations endemic for the 5 PC-NTDs, 72 (68.6%) are co-endemic for 2 or more diseases and could benefit from drug coadministration during PC. All 15 survey respondents reported coadministering medications during PC. Reported responses to a child refusing to take medicine included: not forcing the child to do so (60.0%), encouraging the child (46.7%), bringing the child back later (26.7%), offering powder for oral suspension (POS) for azithromycin (13.3%), and having parents or community members intervene to calm the child (6.7%). Conclusions Coadministration of NTD drugs during PC appears to be increasingly common. Safety of coadministered PC drugs requires attention to choking prevention, use of approved drug combinations, and increased access to age-appropriate drug formulations.